2012
DOI: 10.1038/ismej.2012.63
|View full text |Cite
|
Sign up to set email alerts
|

The metatranscriptome of a deep-sea hydrothermal plume is dominated by water column methanotrophs and lithotrophs

Abstract: Microorganisms mediate geochemical processes in deep-sea hydrothermal vent plumes, which are a conduit for transfer of elements and energy from the subsurface to the oceans. Despite this important microbial influence on marine geochemistry, the ecology and activity of microbial communities in hydrothermal plumes is largely unexplored. Here, we use a coordinated metagenomic and metatranscriptomic approach to compare microbial communities in Guaymas Basin hydrothermal plumes to background waters above the plume … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
168
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 145 publications
(190 citation statements)
references
References 73 publications
14
168
1
Order By: Relevance
“…The balance of DNA reads in background versus plume was more variable, and in some cases, much higher in background than plume (Supplementary Figure S3). In terms of the whole community, these MGI small subunit (SSU) rRNA genes were the most abundantly represented Archaea in both plume and background metatranscriptomic data sets (Lesniewski et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The balance of DNA reads in background versus plume was more variable, and in some cases, much higher in background than plume (Supplementary Figure S3). In terms of the whole community, these MGI small subunit (SSU) rRNA genes were the most abundantly represented Archaea in both plume and background metatranscriptomic data sets (Lesniewski et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Once on deck, plume and background waters were immediately filtered by N 2 gas pressure onto 0.2-mm pore size, 142-mm diameter polycarbonate filters, and fixed and frozen in RNAlater as previously described (Dick et al, 2009b;Dick and Tebo, 2010). Further details of sample processing, locations and environmental conditions are provided in Supplementary Table S1 and in Lesniewski et al (2012). Plume-1 and Plume-2 were used for genomics, whereas Plume-3 and Plume-4 were transcriptomics samples from the plume.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To compare the results among the different data sets, the number of reads was normalized considering the size of the contig and of the collection (number of reads per kilobase per gigabase of the collection). The meso and bathypelagic metagenome collections screened were: Marmara Sea-1000 m (Quaiser et al, 2011), Matapan-Vavilov Deep in the Mediterranean Sea-4900 m (Smedile et al, 2012), North Pacific subtropical gyre-ALOHA station-4000 m (Konstantinidis et al, 2009), Guaymas Basin hydrothermal vent in the Gulf of California (Lesniewski et al, 2012) and a metagenome obtained at 800 m in the South Atlantic Gyre (Swan et al, 2014).…”
Section: Metagenomic Recruitmentmentioning
confidence: 99%
“…These studies often revealed the dominance of archaeal over bacterial ammonia oxidizers (Francis et al, 2005;Wuchter et al, 2006;Mincer et al, 2007;Agogué et al, 2008;Newell et al, 2013). Further support for the strong role for AOA in nitrification comes from observations of the co-occurrence of archaeal amoA in areas of nitrification activity (Caffrey et al, 2007;Beman et al, 2008;Alves et al, 2013) and from metatranscriptomic studies (Baker et al, 2012;Lesniewski et al, 2012). However, to determine the actual contribution and impact of AOA on the nitrogen cycle requires measurements of ammonium oxidation rates, as they cannot be deduced from transcript abundance alone (Mu mann et al, 2011), given that quantification is influenced by, for example, mRNA degradation during sampling (Feike et al, 2012) and, in addition, may not inevitably reflect environmental activity.…”
Section: Introductionmentioning
confidence: 99%